PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP MINAT BELI BATIK BESUREK PADA TOKO SARI RASA - Epa Susanti; Adi Sismanto (UM. Bengkulu, 2021)
This study entitled The effect of Product Price and Quality on Interest in Buying Besurek Batik by Sari Rasa Store Consumers at Soekarno Hatta Street of Anggut Bengkulu City. The formulation of the problem of this research is whether the Price and Quality of Product have a effect on the Interest in Buying Besurek Batik on Sari Rasa Bengkulu Consumer. The purpose of this study is to determine that the effect of Price and Product Quality significantly influence Interest in Buying Besurek Batik.This research was conducted on Besurek Batik Consumers at the Bengkulu City Sari shop. The research was carried out for 13 days. The population of this study was Consumer Batik Besurek At Bengkulu City Sari Rasa Shop, while the sample of this study wass the Consumer Batik Besurek At the City of Bengkulu Sari Rasa Shop, amounting to 91 respondents. The study was conducted in quantitative methods.Based on the analysis of the study, the results of the study can be concluded that respondents' perceptions on Price (X1) and Product Quality (X2) affect the Purchase Interest (Y) with the results of multiple linear regression of Â Y = 2.106 + 0.392 (X_1) + 0.156 (X_2). And the coefficient of determination of R2 = 0.555 or 55.5%. ThroughÂ hypothesis testing in the same time, (simultaneous) and individually (partial)this study using the f test and t test, Price (X1) and Product Quality (X2) = 0.000. This means that the fsig value <0.050 shows a simultanous effect which was significant.Â Keywords: Price, Product Quality and Purchase Interest.